The performance of a gamma-type stirling water dispenser with twin wavy plate heat exchangers - Ammar S. Easa; Wael M. El-Maghlany; Mohamed M. Hassan; Mohamed T. Tolan (Case Studies in Thermal Engineering, 2022)
Today, households increasingly depend on water dispensers as necessary appliances. In this way, the demand for water dispensers with environmentally friendly systems is rising around the globe because there are no eco-friendly alternative water dispensers in the global market as alternatives to vapor compression refrigeration systems. In the present work, the improved Stirling water dispensers for cold and hot water are presented as an environmentally friendly alternative. A gamma-type Stirling water dispenser is improved by integrating twin wavy plate heat exchangers with varying dimensions. A thermodynamic model is developed to carry Schmitt's vision of overcoming the Stirling water dispenser to fruition. The suitable sizes of both heat exchangers are determined to achieve higher heat removal rates and a higher coefficient of performance (COP). Due to the heat exchanger's optimal size, the water cooler generates a cooling load of about 1.4 kW and a heating load of about 4 kW. A suitable and adequate tendency is identified by comparing the data from the past and the present. The performance of the gamma Stirling water dispenser was improved by about 22% as a result of using twin wavy plate heat exchangers.